2022
DOI: 10.3390/plants11050642
|View full text |Cite
|
Sign up to set email alerts
|

Sea Buckthorn (Hippophae rhamnoides) Waste Biomass after Harvesting as a Source of Valuable Biologically Active Compounds with Nutraceutical and Antibacterial Potential

Abstract: For sustainable sea buckthorn (Hippophae rhamnoides) berry production, the task at hand is to find an application for the large amount of biomass waste arising at harvesting. Sea buckthorn (SBT) vegetation is currently poorly studied. The purpose of this research was to assess the composition and potential of SBT twigs as a source of valuable biologically active substances. Water and 50% EtOH extracts of twigs of three Latvian SBT cultivars with a high berry yield and quality, popular for cultivation in many c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…The cytotoxicity was evaluated to determine the toxic concentration of the extracts and PACs and compared with the anti-microbial concentration observed (MIC) for further analysis of their application in anti-microbial therapy [ 28 , 41 ]. Cytotoxicity of all SBT extracts was tested at a concentration range of 0.0313–4.0 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxicity was evaluated to determine the toxic concentration of the extracts and PACs and compared with the anti-microbial concentration observed (MIC) for further analysis of their application in anti-microbial therapy [ 28 , 41 ]. Cytotoxicity of all SBT extracts was tested at a concentration range of 0.0313–4.0 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Our preliminary studies of the chemical composition of extracts isolated from the waste biomass of sea buckthorn (SBT) and other wood species (grey alder, black alder, willow, pine) by water and aqueous ethanol solutions showed that the PACs are the dominant polyphenolic compounds in the extracts [ 27 ]. In previous research, it was shown that SBT twigs are a valuable and cheap source of PACs, and they have higher anti-microbial activity than extracts by themselves [ 28 ]. In a range of European countries such as Latvia, Estonia, Romania, and Germany, as well as in Canada and China where SBT is cultivated on plantations, a large volume of underutilized lignocellulosic biomass waste forms as a result of agrotechnical measures carried out for SBT twice per year, at yearly industrial harvesting of the berries, which includes cutting the whole branch (20% of the berries’ mass) and pruning (90% of SBT plantation biomass every fourth year, almost a full cut of the whole shrub tree) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…CTs content in the extracts was measured by the butanol–HCl method [ 35 ] using procyanidin dimer B2 as a reference compound. Amounts of 6 mL of acid butanol (5% ( v / v ) concentrated HCl in n-butanol) and 0.2 mL of iron reagent ( w / v ) (FeNH 4 (SO 4 ) 2 ∙12 H 2 O in 2 M HCl) were added to 1 mL of the extract aliquots whilst stirring the tube without heating and allowing it to be heated in a water bath at 80 °C for 50 min.…”
Section: Methodsmentioning
confidence: 99%
“…The total amounts of the carbohydrate in the extracts were determined using GC analysis after hydrolysis, reduction, and acetylation as described by Janceva et al [ 35 ]. Gas chromatographic analysis was performed using an Agilent 6850 Series: column—DB-1701; length—30 m; internal diameter—0.25 mm; layer thickness—0.25 µm.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, special attention is paid to the complex and waste-free processing of SBT with the maximum extraction of biologically active substances and the expansion of the range of preparations from the SBT (Janceva et al 2022). In folk medicine, a decoction of leaves is used to treat gastrointestinal diseases, ulcers, and microbial infections (Suryakumar and Gupta 2011;Yue et al 2017;Letchamo et al 2018).…”
Section: Introductionmentioning
confidence: 99%